Make way for ducklings - McCloskey, Robert, 1914-2003. (New York : Scholastic Inc. by arrangement with The Viking Press, 1969)
Mr. and Mrs. Mallard proudly return to their home in the Boston Public Garden with their eight offspring.
Keywords: Caldecott Medal; Ducks -- Juvenile fiction; Boston (Mass.) -- Juvenile fiction